2019
DOI: 10.20431/2454-7999.0503001
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of Phytochemical Constituents in Methanol Extract of Wood Bark from Durio Zibethinus Murr

Abstract: Durio zibethinus Murr. (Durian), a medicinally important plant belongs to the family Bombacaceae. Traditionally the decoctions of the leaf and root have believed to show antipyretic effect and can also be used as a febrifuge and anti-malarial agent. In the present study, the preliminary phytochemical screening of secondary metabolites in the wood bark of Durio zibethinus was investigated using standard methods. The methanol extract of the wood bark was fractionated into four combined fractions (F1-F4) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furo [2, 3-c] pyridine, 2, 3-dihydro-2,7-dimethyl is yet another compound to be mentioned in this context. The identified compound is used in dyes, flavor, fragrances, pharmaceuticals, agrochemicals and as veterinary products [10]. GC-MS analysis of leaves of Hugonia mystax L. Identified a phytochemical compound 11,14,17-Eicosatrienoic acid, methyl ester having bioactivities anti-arthritic, anti-coronary and antiinflammatory (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furo [2, 3-c] pyridine, 2, 3-dihydro-2,7-dimethyl is yet another compound to be mentioned in this context. The identified compound is used in dyes, flavor, fragrances, pharmaceuticals, agrochemicals and as veterinary products [10]. GC-MS analysis of leaves of Hugonia mystax L. Identified a phytochemical compound 11,14,17-Eicosatrienoic acid, methyl ester having bioactivities anti-arthritic, anti-coronary and antiinflammatory (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Diethyl Malonate Pharmaceuticals It is also used to produce the fungicide simoxanil and dextromethorphan cough treatment [32].…”
Section: Analysis Of Gc-ms For Pure Alcoholic Plant Extractsmentioning
confidence: 99%
“…Its fruit pulp may be a reliable source of fiber, dietary fat, proteins, and carbohydrates. [14]. It has also been revealed that durian seed, pulp, and peel flour are endowed with nutritional, structural, antiinflammatory, and antioxidant properties [15,16].…”
Section: Introductionmentioning
confidence: 99%